Olfactory loss and brain connectivity after COVID‐19 - Esposito, Fabrizio; Cirillo, Mario; De Micco, Rosa; Caiazzo, Giuseppina; Siciliano, Mattia; Russo, Andrea Gerardo; Monari, Caterina; Coppola, Nicola; Tedeschi, Gioacchino; Tessitore, Alessandro (Human brain mapping, 2022)
To address the impact of COVID‐19 olfactory loss on the brain, we analyzed the neural connectivity of the central olfactory system in recently SARS‐CoV‐2 infected subjects with persisting olfactory impairment (hyposmia). Twenty‐seven previously SARS‐CoV‐2 infected subjects (10 males, mean age ± SD 40.0 ± 7.6 years) with clinically confirmed COVID‐19 related hyposmia, and eighteen healthy, never SARS‐CoV‐2 infected, normosmic subjects (6 males, mean age ± SD 36.0 ± 7.1 years), were recruited in a 3 Tesla MRI study including high angular resolution diffusion and resting‐state functional MRI acquisitions. Specialized metrics of structural and functional connectivity were derived from a standard parcellation of olfactory brain areas and a previously validated graph‐theoretic model of the human olfactory functional network. These metrics were compared between groups and correlated to a clinical index of olfactory impairment. On the scanning day, all subjects were virus‐free and cognitively unimpaired. Compared to control, both structural and functional connectivity metrics were found significantly increased in previously SARS‐CoV‐2 infected subjects. Greater residual olfactory impairment was associated with more segregated processing within regions more functionally connected to the anterior piriform cortex. An increased neural connectivity within the olfactory cortex was associated with a recent SARS‐CoV‐2 infection when the olfactory loss was a residual COVID‐19 symptom. The functional connectivity of the anterior piriform cortex, the largest cortical recipient of afferent fibers from the olfactory bulb, accounted for the inter‐individual variability in the sensory impairment. Albeit preliminary, these findings could feature a characteristic brain connectivity response in the presence of COVID‐19 related residual hyposmia. A structural and functional neural connectivity analysis of the central olfactory system was performed in previously SARS‐CoV‐2 infected subjects with persisting olfactory impairment. An increased neural connectivity within the olfactory cortex was associated with a recent SARS‐CoV‐2 infection. The functional connectivity of the anterior piriform cortex accounted for the inter‐individual variability in the sensory impairment, suggesting a characteristic brain connectivity response in the presence of COVID‐19 related residual hyposmia.